Systems and the extent of the thought of Imam Badeezaman Said Nursi - Elatrash, Radwan Jamal Yousef (2019)
This study aims at exploring the parameters of the indite theory of Imam Nursi, the study tries to such expectation through a near-full extrapolation off the letter of light (Risale-i Nur). Imam Nursi in his epistles confirms the importance of studying the miracles aspects of the Quran, Imam Nursi agrees with famous scholar of rhetorics that the secret of the miracles Quran in the indite theory. The method followed in his study are inductive and analytical. That study tries to shed light on the origins of this theory since jurjany, jahiz wasiti bakillani and others. Imam Nursi benefited from all this studies, and so he’s was enable to build his new character as the new saeed. Imam Nursi was distinguished by his admiration of Jurjany. And this admiration made Nursi to follow him, by following Jurjany Imam Nursi was able to offer a great detailed work in interpretations of the holy Quran. The important aspect that characterizes Imam Nursi in the combination of the tremendous spiritual energy and his creature language knowledge. This ability of Nursi ena bled him to explore the miracles aspects of the indite theory of the holy Quran.